FORMULASI DAN EVALUSI MUTU FISIK SABUN BATH BOMB EKSTRAK DAUN DADANGKAK (Hydrolea spinosa L.) - Rakhmadhan Niah; Novia Ariani; Erna Prihandiwati (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2023)
Dadangkak contains secondary metabolite compounds including Alkaloids, Steroids and Flavonoids. One of the compounds, namely flavonoids, has activity that can inhibit bacterial growth. The purpose of the study was to determine the effect of dadangkak leaf extract on bath bomb soap preparations and to determine the physical quality of bath boom soap dadangkak leaf extract. This research is a non-experimental research conducted at the STIKES ISFI Banjarmasin. The study sample was dadangkak leaf extract. The research bath boom soap formulation then an evaluation of physical properties consisting of organoleptis test, soluble time, foam height, pH, specific gravity and alkali-free test. The data obtained is compared with SNI. The results of the physical properties test in formula 2 meets the requirements of physical properties with the following results pH 10; Free alkali test 0.06%; Specific gravity test 1.03g/mol; Froth height test 66 mm; Viscosity test 960 mPas. The conclusion of the study found that the formula that meets the requirements for the best physical properties of soap is formula 2 according to the s SNI 06-4085-1996.